2015
DOI: 10.1161/circoutcomes.114.001240
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Utility of Taking Pills for Cardiovascular Prevention

Abstract: Background-The decrease in utility attributed to taking pills for cardiovascular prevention can have major effects on the cost-effectiveness of interventions but has not been well studied. We sought to measure the utility of daily pill-taking for cardiovascular prevention. Methods and Results-We conducted a cross-sectional Internet-based survey of 1000 US residents aged ≥30 in March 2014. We calculated utility values, using time trade-off as our primary method and standard gamble and willingnessto-pay techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 37 publications
2
65
0
Order By: Relevance
“…This is consistent with the current methods of eliciting DTDs, which often use time-trade-off exercises (with questions spanning different hypothetical time periods, typically 10 years) to estimate the utility decrement to use for each 1-year time period. 185,[194][195][196] …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the current methods of eliciting DTDs, which often use time-trade-off exercises (with questions spanning different hypothetical time periods, typically 10 years) to estimate the utility decrement to use for each 1-year time period. 185,[194][195][196] …”
Section: Discussionmentioning
confidence: 99%
“…Three published empirical studies that relate to the concept of DTD were identified through the search strategy [6,8,9]; and one was found via reference list searching [10]. Gage et al find a disutility directly associated with taking warfarin of 0.003 and no disutility associated with taking aspirin when using a time-trade off method in patients (n=70) with atrial fibrillation [10].…”
Section: Elicitation Of Dtdsmentioning
confidence: 99%
“…Gage et al find a disutility directly associated with taking warfarin of 0.003 and no disutility associated with taking aspirin when using a time-trade off method in patients (n=70) with atrial fibrillation [10]. More recently, using time trade off (TTO) methods to elicit values, Hutchins et al found DTDs of 0.01 (95% CI: 0.008 to 0.013) in US residents (n=1000) and 0.003 (95% CI: 0.002 to 0.004) in US healthcare employees (n=708) for a scenario involving one pill per day for life which had no costs or side effects [8,9]. In both papers, standard gamble and willingness to pay methods were also used to elicit disutilities and gave comparable results.…”
Section: Elicitation Of Dtdsmentioning
confidence: 99%
“…Recent evidence suggests that patients are likely to decline statin treatment, even if it may potentially add years to their lives. 3 In fact, 21% of adults considering would pay $1000 or more for information to avoid taking a pill each day for the rest of their lives. 3 These concerns are emphatically countered by arguments that these thresholds do not mandate a statin prescription rather specifically calls for clinician-patient discussion.…”
Section: Article See P 501mentioning
confidence: 99%
“…3 In fact, 21% of adults considering would pay $1000 or more for information to avoid taking a pill each day for the rest of their lives. 3 These concerns are emphatically countered by arguments that these thresholds do not mandate a statin prescription rather specifically calls for clinician-patient discussion. However, I respectfully question, are we putting too much onus on patients to deal with these uncertain risk estimates, without arming them with tools to facilitate better informed decisions?…”
Section: Article See P 501mentioning
confidence: 99%